STUDY RELOCATION EARTHQUAKE HYPOCENTERS IN PALU KORO AND MATANO FAULT ZONE USING GEIGER METHOD - Azizah, Kuni; Susilo, Adi; Rachman, Tri Deni (Physics Student Journal, 2014)
We have conducted research about seismic activity on Palu Koro  and Matano Fault Zone. This research conducted to relocate earthquake hypocenters that occurred in both fault zone, in order to obtain position of hypocenters more accurately. The data of research are 141 earthquakes with 683 P wave arrival times which is occured for a year in 2013. The method of research is Geiger method with Coupled Velocity-Hypocenter model. This is a method for earthquake relocation, determination velocity model of seismic wave in the 1D subsurface, and correction of stations simultaneously using  Geiger principle. The data processing uses Velest33 software. The results show new position of hypocenters better than before. It is  shown by the decreased travel time residuals, i.e from 0.954 second to 0.69 second. The position of hypocenters which have been relocated is closer to the fault zone.The new position of hypocenters have  accuracy up to 0.01 km. The new model of P-wave velocity in 1D  has  velocity slower than the initial model. There are 8 stations in research area that have station correction values range between -0.96 second to 0.4 second. Correction station is dominated by a negative correction value with the PCI station as a reference station. Keyword : Palu Koro, Matano, relocation, Geiger, Velest33